Systemic Lupus Erythematosus and Its Association with Hemophagocytic Syndrome as an Initial Manifestation - CASTILLO, Jorge Medina (Maedica (Bucur), 2020)
Introduction: Hemophagocytic syndrome (HS) is a potentially fatal hyperinflammatory condition characterized by excessive activation of macrophages and T cells. Systemic lupus erythematosus (SLE) is an autoimmune condition that predisposes to HS. The appearance of SLE and HS is rare. Clinical case: A 16-year-old male presented with fever for one month and lymphadenopathy prior to admission. During evaluation, the patient accumulated 10 points required by EULAR/ACR 2019 for classifying the condition as SLE. Hemophagocytosis was observed in the bone marrow aspirate. The diagnosis of HS secondary to SLE was concluded. Under treatment with intravenous methylprednisolone and mycophenolic acid, symptoms improved and the patient was subsequently discharged. Discussion: The most typical findings of HS include fever, hepatosplenomegaly, and cytopenias, with lymphadenopathy being the least common. The characteristics of SLE and HS are very similar, making it difficult to differentiate between these two entities. Conclusion: Although HS is not one of the frequent manifestations of SLE, a high suspicion of its possible association with SLE must be maintained for timely treatment.